Reflection on Data Error Identification Methods for Field Survey Data on Commuter Train Passenger Travel Behavior - Hitapriya Suprayitno; Ria Asih Aryani Soemitro (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2019)
Good understanding of Demand Behavior is important for Infrastructure and Facility Planning. Therefore, Field Survey for Travel Behavior Characterisitcs on Commuter Train Passenger is very important. The data collected and processed must be correct data. Meanwhile errors could easily happen in data collection and tabulation. How is the method to identify the data error. Experiment indicates several following methods : using spread-sheet software is strongly suggested for easiness to develop the whole process, establish numerical data tabulation for data error identification easiness, etablish code for data back-tracked, develop field survey data table, develop data error possibilities tabel, develop a error logical tests, develop spreadsheet logical test function, do error identification calculation.